Synthesis, photophysical and electrochemical properties of novel hexadeca-substituted phthalocyanines bearing naphthoxy groups - KOCA, ATIF (ELSEVIER SCI LTD, 2017)
The synthesis and characterization of a novel tetra-substituted phthalonitrile together with hexadecasubstituted metal-free and metallo phthalocyanines bearing naphthoxy groups in peripheral positions and hexyloxy groups in non-peripheral positions were described. Aggregation properties of phthalocyanine compounds were investigated in a concentration range of 1.4 x 10(-5) M to 4 x 10(-6) M. The energy transfer to phthalocyanine core and radiative decays of the naphthoxy emission and phthalocyanine core were examined. Electrochemistry of the complexes was studied with cyclic voltammetry and square wave voltanimetry techniques. While zinc phthalocyanine (ZnPc) showed two phthalocyanine-based oxidation and two phthalocyanine-based reduction processes, cobalt phthalocyanine (CoPc) illustrated a metal-based and a phthalocyanine-based reductions and one metal-based and two phthalocyanine-based oxidation processes. Redox reactions of CoPcs are electrochemically and chemically reversible, while the reduction processes of ZnPc are reversible and the oxidation processes of ZnPc are quasi reversible processes. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Hexadeca-substitution; Energy transfer; Naphthol; Electrochemistry; METAL-FREE; PHOTOCHEMICAL PROPERTIES; ZINC PHTHALOCYANINE; SPECTROELECTROCHEMICAL CHARACTERIZATION; AGGREGATION BEHAVIOR; COBALT; MANGANESE; METALLOPHTHALOCYANINES; FUNCTIONALITIES; DERIVATIVES